THE EFFECT OF CLIMBING UP AND DOWN STAIRS EXERCISE ON VO2 MAX IN YOUNG ADULTS (AGE 18-22 YEARS) - Anafatun Ihtammaliya; Yosef Purwoko; Buwono Puruhito; Yuswo Supatmo (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background : One of the example of aerobic exercise that is easy and safe is climbing up and down stairs. But with time, people prefer using escalators or elevators to stairs. Whereas, climbing up and down stairs exercise can improve physical fitness which can be assessed from the VO2 max. Aim : To find out the effect of climbing up and down stairs exercise on VO2 max in young adults. Method : This research used Quasi Experimental with pre-test and post-test non-equivalent group method. The sample was medical students of Faculty of Medicine, Diponegoro University (n=36) age 18-22 years that meet the inclusion criteria. The sample was divided into 2 groups, control and treatment groups each consisting of 18 people. The VO2 max was assessed using Multistage Fitness Test (Bleep Test). Statistical analysis with Saphiro-Wilk test, paired T test, Wilcoxon test, unpaired T test, and Mann Whitney test. Result : There was a significant difference of VO2 max before and after climbing up and down stairs exercise in experimental group (p=0.001) and not significant in control group (p=0.181). There was a significant difference of the difference in VO2 max pre-posttest in experimental group and control group (p = 0.001). Conclusion : Six weeks of climbing up and down stairs exercise increases VO2 max in young adults.Keywords : VO2 Max, Climbing Up and Down stairs Exercise, Multistage Fitness Test (Bleep Test)